Non-targeted effects induced by ionizing radiation: Mechanisms and potential impact on radiation induced health effects. Issue 1 (1st January 2015) - Morgan, William F.; Sowa, Marianne B.
Highlights: Cell-to-cell communication between irradiated cells and non-irradiated cells (NTE's) and its potential impact on human health. Speculation on the factors that might be involved in communicating responses from irradiated cells to non-irradiated cells and eliciting an effect. Relationships between irradiated cells and non-irradiated cells and the implications for delayed health effects. Abstract: Not-targeted effects represent a paradigm shift from the "DNA centric" view that ionizing radiation only elicits biological effects and subsequent health consequences as a result of an energy deposition event in the cell nucleus. While this is likely true at higher radiation doses (>1 Gy), at low doses (<100 mGy) non-targeted effects associated with radiation exposure might play a significant role. Here definitions of non-targeted effects are presented, the potential mechanisms for the communication of signals and signaling networks from irradiated cells/tissues are proposed, and the various effects of this intra- and intercellular signaling are described. We conclude with speculation on how these observations might lead to and impact long-term human health outcomes.